1991
DOI: 10.1111/j.1439-0329.1991.tb00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ammonium and nitrate on mycorrhizal seedlings of Pinus sylvestris1

Abstract: The effects of ammonium sulphate and sodium nitrate on Pinus sylvestris seedlings inoeulated with Paxillus involutus and Suillus hovinus were investigated. Weekly fertilization (26 weeks) positively affected the plant dry weight, but inhibited the mycorrhizal formation and decreased the root length/weight ratio. Ammonium treatments affeeted the seedlings more positively and the myeorrhizas more negatively than nitrate did. The effects on seedlings inoeulated with P. involutus were more pronounced than on those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…In some studies a stronger inhibition of mycorrhizal formation was observed for NO $ − (Bigg, 1981 cited in Alexander (1983) ; Rudawska, 1986 ;Holopainen & Heinonen-Tanski, 1993), whereas in other studies mycorrhizal formation was adversely affected by NH % + (Jentschke, Godbold & Hu$ ttermann, 1989 ;Termorshuizen & Ket, 1991 ;Wallander & Nylund, 1991). These contradictory results are probably due to strain-specific variations in the ability of ECM fungi to utilize NO $ − or NH % + (France & Reid, 1984 ;Ho & Trappe, 1980).…”
Section: Effects Of Varied N Treatments On Ectomycorrhizas In Plantatmentioning
confidence: 62%
See 3 more Smart Citations
“…In some studies a stronger inhibition of mycorrhizal formation was observed for NO $ − (Bigg, 1981 cited in Alexander (1983) ; Rudawska, 1986 ;Holopainen & Heinonen-Tanski, 1993), whereas in other studies mycorrhizal formation was adversely affected by NH % + (Jentschke, Godbold & Hu$ ttermann, 1989 ;Termorshuizen & Ket, 1991 ;Wallander & Nylund, 1991). These contradictory results are probably due to strain-specific variations in the ability of ECM fungi to utilize NO $ − or NH % + (France & Reid, 1984 ;Ho & Trappe, 1980).…”
Section: Effects Of Varied N Treatments On Ectomycorrhizas In Plantatmentioning
confidence: 62%
“…Termorshuizen & Ket (1991) found no effect on the percentage of pine root tips mycorrhizal with Paxillus involutus at 10 kg N ha −" yr −"…”
Section: Effects Of Increased Nitrogen Availability On Mycorrhizal Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with findings of Väre (1990), who found that different doses of N fertilization had no effect on growth of Scots pine seedlings. Nitrogen nutrition research has always been subjected to conflicted results that may be caused by differences in the nitrogen nutrition of mycorrhizal fungal species and their isolates (Termorshuizen and Ket, 1991). Some authors found greater below-biomass of plants at low N availability (Colpaert et al, 1999;Raich and Nadelhoffer, 1989) but even if the below-biomass was greater there was no significant differences in the above-ground biomass (Hobbie and Colpaert, 2003).…”
Section: Discussionmentioning
confidence: 96%